2018
DOI: 10.1038/s41467-018-04428-w
|View full text |Cite
|
Sign up to set email alerts
|

Rhodopsin-cyclases for photocontrol of cGMP/cAMP and 2.3 Å structure of the adenylyl cyclase domain

Abstract: The cyclic nucleotides cAMP and cGMP are important second messengers that orchestrate fundamental cellular responses. Here, we present the characterization of the rhodopsin-guanylyl cyclase from Catenaria anguillulae (CaRhGC), which produces cGMP in response to green light with a light to dark activity ratio >1000. After light excitation the putative signaling state forms with τ = 31 ms and decays with τ = 570 ms. Mutations (up to 6) within the nucleotide binding site generate rhodopsin-adenylyl cyclases (CaRh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
69
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 52 publications
4
69
0
2
Order By: Relevance
“…1B and [20]). In many of our crystallization conditions, we obtained crystals with unit cells comprising monomeric or unconventional head-tohead disulphide bond-stabilized dimeric assemblies that have been reported by others [11,20]; these will not be discussed further.…”
Section: Structure Of the Cagcágtpáca 2+ Complexmentioning
confidence: 95%
See 3 more Smart Citations
“…1B and [20]). In many of our crystallization conditions, we obtained crystals with unit cells comprising monomeric or unconventional head-tohead disulphide bond-stabilized dimeric assemblies that have been reported by others [11,20]; these will not be discussed further.…”
Section: Structure Of the Cagcágtpáca 2+ Complexmentioning
confidence: 95%
“…Mechanistic insights into the activity of class III NCs have been derived from dozens of crystal structures of AC domains in a ligand-free form or bound to substrate-based inhibitors, substrates or ATP analogues in various conformations [3][4][5][6][7][8][9][10][11]. Structural analysis suggests that the AC dimer undergoes a functional conformational change that involves 'closing' of the active site region that brings the catalytic residues distributed across the subunit interface into the proper register.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although HeRs share low sequence identity with the other rhodopsins and adopt the inverted membrane topology, the crystal structures revealed that HeR comprises 7TMs with the retinal chromophore, as in the other rhodopsins [39][40][41] . Unlike these rhodopsins, the enzyme rhodopsins have long N-termini, and are predicted to have 1-2 additional transmembrane helices 11,12,42 , while the existence of TM0 and its function still have remained to be elucidated. The current Rh-PDE structures revealed that TM0 certainly exists and plays key roles in the stable retinal binding to TM1-7 and photoactivation ( Fig.…”
mentioning
confidence: 99%